Quality assurance for point-of-care testing in Mozambique's National Health Service - Patrina Chongo; Nádia Sitoe; Sofia Viegasa; Isabel Pinto; Admiro Macave; Fernando Sitoe; Adolfo Vubila; Nédio Mabunda; Eduardo S. Gudoa; Ilesh V. Jani (AOSIS, 2016)
No abstract available.